2014
DOI: 10.1164/rccm.201309-1735oc
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-disordered Breathing in Hispanic/Latino Individuals of Diverse Backgrounds. The Hispanic Community Health Study/Study of Latinos

Abstract: Rationale: Hispanic/Latino populations have a high prevalence of cardiovascular risk factors and may be at risk for sleep-disordered breathing (SDB). An understanding of SDB among these populations is needed given evidence that SDB increases cardiovascular risk.Objectives: To quantify SDB prevalence in the U.S. Hispanic/Latino population and its association with symptoms, risk factors, diabetes, and hypertension; and to explore variation by sex and Hispanic/ Latino background.Methods: Cross-sectional analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
190
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 224 publications
(201 citation statements)
references
References 46 publications
(46 reference statements)
7
190
2
2
Order By: Relevance
“…1 Recent population-based studies have shown an alarming increase in the prevalence of OSA, with reported rates of moderate-tosevere OSA (defined as an apnea-hypopnea index (AHI) ≥ 15 events/h) up to 50%. [2][3][4][5] The rise in prevalence is likely due to a combination of factors, such as the obesity epidemic, increased sensitivity of sleep study recording sensors and reduced stringency of scoring criteria as a result of updates. 6,7 The majority of OSA subjects in these studies were previously undiagnosed, suggesting a large burden of sleep apnea subjects that remains unrecognized in the general population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Recent population-based studies have shown an alarming increase in the prevalence of OSA, with reported rates of moderate-tosevere OSA (defined as an apnea-hypopnea index (AHI) ≥ 15 events/h) up to 50%. [2][3][4][5] The rise in prevalence is likely due to a combination of factors, such as the obesity epidemic, increased sensitivity of sleep study recording sensors and reduced stringency of scoring criteria as a result of updates. 6,7 The majority of OSA subjects in these studies were previously undiagnosed, suggesting a large burden of sleep apnea subjects that remains unrecognized in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The majority of OSA subjects in these studies were previously undiagnosed, suggesting a large burden of sleep apnea subjects that remains unrecognized in the general population. 4,5 OSA subjects in the general population are unique in two aspects. First, the prevalence of OSA is lower as compared to referral populations such as preoperative or sleep clinic patients.…”
Section: Introductionmentioning
confidence: 99%
“…2 We recently reported the prevalence of mild, moderate, and severe SA in the US Hispanic/Latino population to be 25.8% (apnea-hypopnea index [AHI] ≥ 5), 9.8% (AHI ≥ 15), and 3.9% (AHI ≥ 30), respectively 1 . SA has been associated with numerous cardiovascular conditions including hypertension, 3 coronary heart disease, 4,5 cardiac arrhythmias, 6 heart failure, 7,8 stroke 9 and sudden death.…”
Section: Introductionmentioning
confidence: 99%
“…Despite increasing awareness of this disorder, the majority of individuals with OSA remain undiagnosed [2,3]. OSA has been associated with numerous long-term health consequences, including cardiovascular, metabolic, and cognitive impairments, as well as increased accident rates and lower quality of life [4].…”
Section: Introductionmentioning
confidence: 99%